2013
DOI: 10.1634/theoncologist.2012-0350
|View full text |Cite
|
Sign up to set email alerts
|

Discordances in Estrogen Receptor Status, Progesterone Receptor Status, and HER2 Status Between Primary Breast Cancer and Metastasis

Abstract: Background. The primary aim of this retrospective study was to investigate intraindividual correlation of estrogen receptor (ER) status, progesterone receptor (PR) status, and HER2 status between primary breast cancer and metastatic breast cancer (mBC). Secondary aims included patients' characteristics, overall survival, feasibility of histopathological evaluation in the metastatic setting, and predictive factors associated with receptors status discordance. Methods. Patients with either biopsy of metastatic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
68
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 29 publications
8
68
0
1
Order By: Relevance
“…Consistent with the literature, we identified less frequent expression of hormone receptor expression in breast cancer brain metastases26, 27, 28—although in a much larger patient cohort and with the novel extension of this to androgen receptor (AR) status. Hormone receptor loss is a known marker of aggressive disease, negative prognosis and limited treatment options.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the literature, we identified less frequent expression of hormone receptor expression in breast cancer brain metastases26, 27, 28—although in a much larger patient cohort and with the novel extension of this to androgen receptor (AR) status. Hormone receptor loss is a known marker of aggressive disease, negative prognosis and limited treatment options.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, c-erb-B2 showed only 4% discordance rate. Chemotherapy, and especially anthracyclinebased chemotherapy, was associated with switch in ER status [14]. In this case, ER and PR showed positivity on metastatic gastric lesion that is agreement with primary breast disease; consistent with metastatic breast carcinoma.…”
Section: Citationsupporting
confidence: 58%
“…Curtit et al [14] compared IHC findings between primary breast malignancy and metastatic lesion after treatment. Forty two patients showed discordance on IHC analysis, a switch in receptor status was verified for ER in 17% and PR in 29%.…”
Section: Citationmentioning
confidence: 99%
“…It is well known that a considerable controversy concerns the issue of hormone receptors (HRs) expression as well as HER2 status between primary breast carcinomas (BC) and metastatic sites from the same patient, as elsewhere reported in literature [1][2][3][4][5]. In particular, the discordance between primary BC and metastases from negative to positive and vice versa potentially affects the treatment regimen [5]; therefore, it has been suggested that neoplastic tissue of metastatic lesions should be systematically re-biopsied to optimally re-assess HR as well as HER2 [1,2,[4][5][6][7][8].In their meta-analysis, focusing on HER2 status, Aurilio et al documented that the pooled discordance proportion with respect to the primary breast tumour was 10% for distant metastases and 6% for loco-regional relapses. Moreover, a different pooled discordant proportion was found on the basis of the different utilised technique, since it was 10% in studies using immunohistochemistry (IHC) and fluorescence in situ hybridisation (FISH), but 5% in studies using IHC only; therefore, they conclude the observed discrepancy was not merely due to technicality.…”
mentioning
confidence: 99%
“…In the paper, the Authors have performed a meta-analysis of the studies published in the literature concerning the discordance rate in oestrogen receptor (ER), progesterone receptor (PgR) and HER2 status between primary tumour and corresponding relapse. It is well known that a considerable controversy concerns the issue of hormone receptors (HRs) expression as well as HER2 status between primary breast carcinomas (BC) and metastatic sites from the same patient, as elsewhere reported in literature [1][2][3][4][5]. In particular, the discordance between primary BC and metastases from negative to positive and vice versa potentially affects the treatment regimen [5]; therefore, it has been suggested that neoplastic tissue of metastatic lesions should be systematically re-biopsied to optimally re-assess HR as well as HER2 [1,2,[4][5][6][7][8].…”
mentioning
confidence: 99%